Oxneriaria pakistanica sp. nov. (Megasporaceae, Pertusariales, Ascomycota) from Darel Valley, Gilgit Baltistan, Pakistan - Iqbal, Muhammad Shahid; Usman, Muhammad; Habib, Kamran; Khalid, Abdul Nasir (Phytotaxa, 2023)
A new species in Megasporaceae, Oxneriaria pakistanica is described and illustrated from Pakistan. A comparative morpho–anatomical study and ITS–based molecular analyses confirmed its position within the recently resurrected genus, Oxneriaria. The taxon has non-zonate thallus, epruinose, distinctly areolate, 0.5–1.8 mm wide areole, grey to whitish grey at upper surface, prothallus absent, 0.1–2 mm in diameter apothecia, taller hymenium 100–155 µm, deeper hypothecium 90–170 µm, broadly ellipsoid to sub-spherical ascospores 10–18 × 7–10 µm size and chemistry unknown substance detected. Its forms a separate branch in the phylogenetic tree and also distinct from the other known taxa of the genus. Oxneriaria pakistanica sp. nov appeared to be a sister specie to Oxneriaria rivulicola. A detailed comparison and a key to all taxa of Oxneriaria is also given.